Health-related Quality of Life Measurement Tools for Lymphedema: A Review of the Literature. Issue 4 (27th April 2022) - Lim, Pelicia; Li, Henry; Neoh, Derek; Ng, Sally Kiu-Huen
Abstract : Background: Lymphedema can significantly affect patients' health-related quality of life (HRQoL). Various quality of life scales have been developed to assess the extent of the disease burden. The purpose of this study is to review various HRQoL instruments that have been used in lymphedema studies and compare their qualities against the COSMIN checklist. Methods: A systematic literature review search was conducted for clinical lymphedema studies published between January 1, 1984, and February 1, 2020, using Pubmed database. All clinical lymphedema studies which used HRQoL instruments as outcome measures were identified. Results: One thousand seventy-six studies were screened—of which, 288 studies were individually assessed. Thirty-nine HRQoL instruments were identified in these clinical lymphedema studies. Of these, there are eight lymphedema-specific questionnaires that cover all HRQoL domains, all of which have been validated for use in lymphedema. We contrasted the two most popular questionnaires [LYMQOL and Upper Limb Lymphedema (ULL)-27] and compared their features. Conclusion: There is currently no ideal lymphedema HRQoL measurement tool available based on the COSMIN criteria. However, our review suggested that LYMQOL and ULL-27 are the most used and most validated instruments at present, but each has their own limitations. We recommend the use of LYMQOL and ULL-27 for future studies to allow direct HRQoL comparison to current literature. Further research is required to develop an optimal HRQoL questionnaire that can ultimately become the gold standard HRQoL instrument for lymphedema.